2008
DOI: 10.1063/1.2973399
|View full text |Cite
|
Sign up to set email alerts
|

Electronic properties of doped silicon nanocrystal films

Abstract: The structural and electrical properties before and after laser annealing of spin-coated films of doped silicon nanocrystals (ncs) produced from the gas phase are presented. While the as-deposited films form a porous network of ncs and show only weak electrical conductivity independent of the doping level, a laser annealing step leads to sintering and melting of the particles and tremendously increases the lateral conductivity. By controlled doping of the initial particles, the conductivity can be further enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(119 citation statements)
references
References 39 publications
6
112
1
Order By: Relevance
“…It is also found that the Si 2p peak can be decomposed into two sub-bands, which is assigned to Si-Si state (E BSi2p =99.6±0.1 eV) and Si-C state (E BSi2p =100.4±0.1 eV), respectively. 15 It is suggested from XPS spectra that the most of Si atoms are bonded to neighboring Si and only small portion of Si are bonded to C atoms. It is noted that the Si/C ratio is almost the same for un-doped and P-doped samples even after thermal annealing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also found that the Si 2p peak can be decomposed into two sub-bands, which is assigned to Si-Si state (E BSi2p =99.6±0.1 eV) and Si-C state (E BSi2p =100.4±0.1 eV), respectively. 15 It is suggested from XPS spectra that the most of Si atoms are bonded to neighboring Si and only small portion of Si are bonded to C atoms. It is noted that the Si/C ratio is almost the same for un-doped and P-doped samples even after thermal annealing.…”
Section: Methodsmentioning
confidence: 99%
“…13,14 Lechner et al fabricated the doped nc-Si films and they obtained the maximum conductivity up to about 5 S/cm with the very small conductivity activation energy. 15 From the view point of device application, it is highly desired to get nc-Si:SiC films with high conductivity at the suitable optical band gap (>2.5 eV) so that they can act as the window layer or the conductive layer in nano-crystalline SiC film-based optoelectronic devices without absorbing incident (or emitted) light too much. 13,16 In our previous work, hydrogenated amorphous silicon carbide (a-SiC:H) films were prepared in a plasma-enhanced chemical vapor deposition (PECVD) system.…”
Section: Introductionmentioning
confidence: 99%
“…Si NCs embedded in SiO 2 are widely investigated for their novel size-dependent electronic and optoelectronic properties [6][7][8][9][10][11][12][13]. In particular, the exploitation of the properties of such systems in real devices demands an accurate control of their doping.…”
Section: Resultsmentioning
confidence: 99%
“…Doping of semiconductor nanostructures has proven to be distinct from the corresponding bulk materials [1][2][3][4][5] and recently great attention has been focused on developing practical methodologies to dope and control the doping properties of Si nanostructures such, as nanoclusters (NCs) [6][7][8][9][10][11][12][13] and nanowires [14][15][16][17], and on developing theoretical approaches to understand these properties [18][19][20][21][22][23]. The control of doping properties of Si nanostructures allows the fabrication of complex nanomaterials characterized by unpreceded electrical and optoelectronic functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…The use of annealing to increase the conductivity of nc-Si films was already known [21,22]. Possible mechanisms include sintering, particle transfer, and even sublimation of nanoparticles from a hot substrate to a cold one [23].…”
Section: Sem Investigationmentioning
confidence: 99%